2015
DOI: 10.3109/00207454.2015.1047016
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain MRI abnormalities and neurodevelopmental outcomes in a rat model of neonatal hypoxia-ischemia

Abstract: Male rats are more vulnerable to the detrimental consequences of HIBI, with more severe nervous reflex deficits, brain injury, memory impairment and hemiplegic paralysis than female rats. Serial neurobehavioral follow-up is still executed on the HIBI infants who is absent of detectable abnormalities in early children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Some studies using HI have shown an effect associated with sex [18][19][20]. Here, when we compared injury scores of male and female mice, we found CD1 males to be more injured than females at P7, but no difference between CD1 males and females at P9 ( Fig.…”
Section: Sex Differencessupporting
confidence: 49%
“…Some studies using HI have shown an effect associated with sex [18][19][20]. Here, when we compared injury scores of male and female mice, we found CD1 males to be more injured than females at P7, but no difference between CD1 males and females at P9 ( Fig.…”
Section: Sex Differencessupporting
confidence: 49%
“…The developmental delay of physical characteristics, i.e., eye opening, ear unfolding, and incisor eruption, along with neurological reflexes, such as cliff aversion, gait, grasp, and limb placing, seem to be dependent on the severity of the injury and independent of sex (Ashwal et al, ; Huang et al, ; Nie et al, ). Motor skills in males appear to be more vulnerable to HI in the negative geotaxis test (Huang et al, ; Waddell et al, ). However, results of the righting reflex test are somehow conflicting, with some reporting that HI females (Peterson et al, ) and others that HI males are more impaired compared with control (Huang et al, ).…”
Section: Sex Differences In Behavioral Outcome and Severity Of Brain mentioning
confidence: 99%
“…Motor skills in males appear to be more vulnerable to HI in the negative geotaxis test (Huang et al, ; Waddell et al, ). However, results of the righting reflex test are somehow conflicting, with some reporting that HI females (Peterson et al, ) and others that HI males are more impaired compared with control (Huang et al, ).…”
Section: Sex Differences In Behavioral Outcome and Severity Of Brain mentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort and animal studies, using hypoxia stimulus and carotid artery occlusion, have demonstrated higher vulnerability to oxygen deprivation injury in male infants born near‐ or full‐term, compared to females (Huang et al, 2016; Waddell et al, 2016). Clinically, sex differences have also been observed following traumatic brain injury, where females were more resistant to neurological deficits (Roof and Hall, 2000).…”
Section: Introductionmentioning
confidence: 99%